Anticoagulant therapy for nodular regenerative hyperplasia in a HIV-infected patient - Bihl, Florian; Janssens, Filip; Boehlen, Francoise; Rubbia-Brandt, Laura; Hadengue, Antoine; Spahr, Laurent (BMC gastroenterology, 2010)
Background Nodular regenerative hyperplasia (NRH) has been recently recognized as an emergent cause of liver disease in HIV-infected patients. NRH may cause non-cirrhotic portal hypertension with potentially severe consequences such as refractory ascites, variceal bleeding and hypersplenism. Obliteration of the small intrahepatic portal veins in association with prothrombotic disorders linked to HIV infection itself or anti-retroviral therapy seem to be the causes of NRH and thus the term HIV-associated obliterative portopathy has been proposed. Case Presentation Here we describe a case of a HIV-infected patient with biopsy-proven NRH and listed for liver transplantation (LT) because of refractory ascites and repeated upper gastrointestinal bleedings. A transjugular intrahepatic portosystemic shunt was placed as a bridge to LT and did not improve liver function. However, anticoagulant therapy with low-molecular-weight heparin (LMWH) was associated with rapid improvement in the liver condition and allowed to avoid LT in this patient. Conclusions Thus, this case underscores the relation between thrombophilia and HIV-associated NRH and emphasizes anticoagulant therapy as possible treatment.